REDEEMING CONSCIENCE - Keenan, James F. (Asian Horizons, 2015)
Since the final report of the extraordinary synod of 2014 made no mention of conscience, this note proposes a notion of socially oriented and accountable conscience as opposed to the contemporary use of conscience among US Catholics, that is, as dissenting from the law. Turning to the European use of conscience that arises from the social remorse of their own conduct in World War II, the note proposes that when the United States finally repents over its racist history, we might begin to see that conscience requires us to enter into solidarity with others and to be vigilant of the threats to our own humanity.